Penerapan Google Sites sebagai Solusi Teknologi Pembelajaran Berbasis Web - Vikenso Ch. S. Taaraaungan; Olfiana Bastian; Tesalonika Maengkom; Grace Christien Sumakul (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
The development of information and communication technology has encouraged the world of education to adapt to the use of digital media in the learning process. One platform that can be utilized effectively is Google Sites, a free website creation service from Google that allows teachers and students to easily create web-based learning media. This article comprehensively discusses the use of Google Sites as a learning medium, including its advantages, disadvantages, and functions in supporting digital learning. In addition, this article also explains the systematic steps in creating a learning site using Google Sites, from planning to publishing the site. The results of the discussion show that Google Sites is a practical, flexible, and collaborative solution in supporting 21st century learning, especially in the context of blended learning and distance learning. Although it has limitations in design and interactivity, the advantages in integrating Google services and ease of use make this platform worthy of adoption in educational environments.